End of days : a Pike Logan novel - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller, 2022)
"Pike Logan must stop a deranged fanatic bent on igniting an international conflagration in this explosive, action-packed thriller from New York Times bestselling author and former special forces officer, Brad Taylor"--